PENGARUH INHIBITOR NATRIUM KROMAT TERHADAP LAJU KOROSI PADA KOMPONEN RADIATOR SISTEM PENDINGIN MOBIL - Khan, Muhammad Akyas; Hadromi, Hadromi (Automotive Science and Education Journal, 2020)
Radiator is one of the engine cooling system components that has leakage problems due to corrosion. The leakage in the cooling system can cause bad effects namely overheating. This study aims to find out the effect of sodium chromate inhibitors (Na2CrO4) can reduce the corrosion rate of car radiator components and find out the type of corrosion that occurs in car radiator components in aquades environment. The research method used is a real experiment. The corrosion testing was conducted by specimens immersing from aluminum radiators. The specimen was immersed in distilled water solution with variations in the addition of sodium chromate inhibitors of 0%, 0.3%, 0.5% and 0.7%. The micro photo testing used an optical microscope to determine the type of corrosion. The analysis in this study is descriptive statistical analysis. The results of this study indicated of the corrosion rate of aluminum in an aquades environment without inhibitors is 0.0084 mmpy. Meanwhile the corrosion rate of aluminum decreased with the addition of sodium chromate inhibitors (0.3% by 0.0053 mmpy, 0.5% by 0.0051 mmpy and 0.7% by 0.0043 mmpy). Thus the use of sodium chromate inhibitors can extend the life / time of using aluminum radiators. While the type of corrosion that occurs is pitting corrosion.